Evaluation Of The Deterioration Of Vegetable Oil Used In Commercial Establishments Of Duque De Caxias - RJ - Thode Filho, Sérgio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708729 The frying process is a simplified, faster and palatable for most people. However, this process causes a number of physical and chemical changes in vegetable oil, causing adverse impacts to human health. The aim of this study was to analyze the quality of the vegetable oil used and reused in nine commercial establishments in Duque de Caxias, RJ. The evaluation of vegetable oil became possible by indexes of acidity and peroxide indicated by Institute Adolf Lutz, which are parameters to check the level of deterioration. As a result, we found high levels of acidity and the presence of peroxides in two of the samples, which makes it important to establish good practice to use, handling and storage of vegetable oil.